Pengaruh Kualitas Penerapan Good Corporate Governance (GCG) terhadap Kinerja Keuangan pada Bank Umum Syariah di Indonesia (Periode 2010-2015) - Angrum Pratiwi (Al-Tijary, 2016)
The purpose of this study to determine the effect of the application of Good Corporate Governance (GCG) on financial performance as measured by the ratio of Capital Adequacy Ratio (CAR), Non Performing Financing (NPF), Return on Assets (ROA), Return on Equity (ROE), Net Income Margin (NIM), Financing Deposits ratio (FDR), and the ratio of Operating Expenses and Operating Income (ROA) at the Islamic Banks. The study population was the whole Islamic Banks that have implemented GCG according to the rules of Bank Indonesia. This research is associative to see the relationship between the variables of one another. The data used are secondary data from the annual report and corporate governance report published by respectively Islamic Banks 2010-2016 period. Samples collected are 10 Islamic banks by the number N = 60. The results showed that the application of GCG is based on data collected had an average of 1:55 to 2:20 that enter into the category of "Good". This means that the quality of GCG implementation in accordance with the BUS 11 indicators that have been set by Bank Indonesia. The results of the t test (partial test) showed that the quality of GCG implementation significant positive effect on the CAR, NPF and ROA. The quality of GCG implementation negatively affects the ROA and ROE significantly. While the statistical test results apparently GCG implementation does not affect the performance ratio of NIM and FDR.